PENERIMAAN, TINGKAT STRES, DAN STRATEGI KOPING IBU TERHADAP PROGRAM KONVERSI MINYAK TANAH KE LPG DI KABUPATEN BOGOR - Latifah, Melly; Juanda, Anne Maria (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The increasing of Indonesian population over years (2,6 million per years) causing increasing demand of energy as something that cannot be avoided. Energy reserve is running low in Indonesia. Energy crisis, which happen in this time, trigger some problems that need new policy especially in public policy. One of step from the government to overcome kerosene crisis is convertion program from kerosene to LPG with purpose to decrease dependence of society about kerosene. The main objective of this research was to analyze the mother’s response of cerosene convertion program to LPG in Bogor Regency. The method of this research was cross sectional study with 80 samples. Analysis data which used was Pearson’s Correlation and Linear Regression. The results of this research showed that those of samples who used LPG have high acceptance level. Higher using of LPG by samples tended to the higher chanced of sample’s stress. There was tendency that samples who did not use LPG so they would not had more stress. There was negative correlation between per capita incomes and quantities of family with acceptance level. Despite of that, only per capita incomes and acceptance level of samples which influenced on coping strategy.